2015
DOI: 10.1016/j.jneumeth.2015.03.022
|View full text |Cite
|
Sign up to set email alerts
|

A novel operant-based behavioral assay of mechanical allodynia in the orofacial region of rats

Abstract: Background Detecting behaviors related to orofacial pain in rodent models often relies on subjective investigator grades or methods that place the animal in a stressful environment. In this study, an operant-based behavioral assay is presented for the assessment of orofacial tactile sensitivity in the rat. New Methods In the testing chamber, rats are provided access to a sweetened condensed milk bottle; however, a 360° array of stainless steel wire loops impedes access. To receive the reward, an animal must … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 42 publications
0
15
0
1
Order By: Relevance
“…Here, animals are trained to drink a reward while forced to place their face through temperature controlled thermal pads. Pain is assessed as a reduction in amount of reward consumed (quantified by number of licks) as well as contacts against the thermal pads [175, 176]. Recent work has shown that nitroglycerin treatment can decrease the amount of licks/contacts in wild type mice [177] indicating an increased sensitivity to thermal orofacial stimulation.…”
Section: Experimental Readouts: Behavioral Assaysmentioning
confidence: 99%
“…Here, animals are trained to drink a reward while forced to place their face through temperature controlled thermal pads. Pain is assessed as a reduction in amount of reward consumed (quantified by number of licks) as well as contacts against the thermal pads [175, 176]. Recent work has shown that nitroglycerin treatment can decrease the amount of licks/contacts in wild type mice [177] indicating an increased sensitivity to thermal orofacial stimulation.…”
Section: Experimental Readouts: Behavioral Assaysmentioning
confidence: 99%
“…Figure 8 also shows that the capsaicin-induced hypersensitivity to 48°C thermal punishment can be alleviated by the transient receptor potential V1 antagonist (E)-3-(4-t-butylphenyl)-N-(2,3-dihydrobenzo[b][1,4]dioxin-6-yl)acrylamide (AMG9810) (30 mg/kg), but not by the κ opioid receptor agonist methyl 4-[2-(3,4-dichlorophenyl)acetyl]-3-(pyrrolidin-1-ylmethyl)piperazine-1-carboxylate (GR89696) (Neubert et al, 2007). This procedure has also been adapted for use in mice (Neubert et al, 2008; Ramirez et al, 2015) and for use with noxious mechanical rather than thermal stimuli (Rohrs et al, 2015).…”
Section: Behavioral Outcome Measures In Analgesic Drug Discoverymentioning
confidence: 99%
“…No fill indicates drug not tested. Citations are not intended to be exhaustive, but rather to illustrate typical outcomes. a Numbers correspond to the following references: 1) Morgan et al, 1999; 2) Craft et al, 2012; 3) Seguin et al, 1995; 4) Neelakantan et al, 2015; 5) Bagdas et al, 2016; 6) Negus et al, 2015; 7) Miller et al, 2011; 8) Stevenson et al, 2006; 9) Matson et al, 2010; 10) Thomas et al, 1992; 11) Vierck et al, 2002; 12) Kangas and Bergman, 2014; 13) Harte et al, 2016; 14) Altarifi et al, 2015; 15) Martin et al, 2017; 16) Hargreaves et al, 1988; 17) Cobos et al, 2012; 18) Kristensen et al, 2017; 19) Sotocinal et al, 2011; 20) Herrera et al, 2018; 21) Martin et al, 2004; 22) Rutten et al, 2014a; 23) Kandasamy et al, 2017; 24) Neubert et al, 2005; 25) Neubert et al, 2006; 26) Balayssac et al, 2014; 27) Rohrs et al, 2015; 28) Ewan and Martin, 2014; 29) Ririe et al, 2018; 30) Nazemi et al, 2012; 31) Erichsen and Blackburn-Munro, 2002; 32) van der Kam et al, 2008; 33) Wilkerson et al, 2018; and 34) Leitl and Negus, 2016.…”
Section: Preclinical Antinociceptive Drug Profilesunclassified
“…The current behavior assays to assess pain sensation in rodents can be broadly classified as operant pain assays, spontaneous pain detection assays, and reflexive withdrawal assays (Barrot, 2012; Le Bars et al, 2001; Mogil, 2009; Yuan et al, 2016). Operant assays typically involve animals’ successfully completing a task or learning to avoid or prefer a chamber that is associated with pro- or anti-nociceptive stimuli or experiences (Hung et al, 2015; Mauderli et al, 2000; Nag and Mokha, 2016; Rohrs et al, 2015). Because these assays require normal learning and memory processes for the animal to report its preference or avoidance, the failure of an animal to learn or remember a pro-nociceptive chamber or task may not necessarily indicate a lack of pain.…”
Section: Introductionmentioning
confidence: 99%